2020
DOI: 10.12788/jhm.3412
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Care Team Perspectives of Telemedicine in Critical Access Hospitals

Abstract: Telemedicine acute care may address issues facing critical access hospitals. This evaluation used web, mail, and telephone surveys to quantitatively and qualitatively assess patient and care team experience with telemedicine in 3 rural critical access hospitals and a large metropolitan tertiary care hospital. Results show that patients, nurses, and clinicians perceived quality of care as high, and they offered feasible recommendations to enhance communication and otherwise improve the experience. Continued wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Hub telehospitalists reported satisfaction with the program, and they perceived the quality of care to be comparable to face‐to‐face encounters; their responses were consistent with those previously reported in an evaluation of telemedicine acute care by JaKa et al 20 Spoke‐site staff, however, had a mixed level of satisfaction, which was different from responses reported by JaKa et al 20 The primary challenges encountered were technological and communication issues, differences in cultures of care between the hub and the spoke sites, and buy‐in from frontline staff. Differences in expectations and unclear role definitions between the local APP and the telehospitalist were identified as contributors to dissatisfaction with the program by the nursing staff.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hub telehospitalists reported satisfaction with the program, and they perceived the quality of care to be comparable to face‐to‐face encounters; their responses were consistent with those previously reported in an evaluation of telemedicine acute care by JaKa et al 20 Spoke‐site staff, however, had a mixed level of satisfaction, which was different from responses reported by JaKa et al 20 The primary challenges encountered were technological and communication issues, differences in cultures of care between the hub and the spoke sites, and buy‐in from frontline staff. Differences in expectations and unclear role definitions between the local APP and the telehospitalist were identified as contributors to dissatisfaction with the program by the nursing staff.…”
Section: Discussionsupporting
confidence: 82%
“…Telehospitalist services (THS) can help deliver high‐quality care to rural residents locally, decrease travel expenses, support hospital volume, and increase healthcare capacity in response to a pandemic 14,17,18 . Only a few studies have described THS (mostly with overnight or cross‐coverage models directed to CAHs), and clinical outcomes have been inconsistently reported 17,19‐21 . Furthermore, no program has been conducted within an integrated health system akin to the VHA.…”
mentioning
confidence: 99%
“…12,23,27,29 JaKa showed that care teams overwhelmingly recommended telemedicine (clinicians = 100% and nurses 95%), were satisfied with communication (>90%), and saw improved cross-coverage and admission processes. 23 Gutierrez 20 reported high satisfaction among telehospitalists (100%) but only 58% satisfaction among clinicians and 30% for nurses at the receiving site. 20 Qualitative evaluations provided additional insight into the value perceived by care teams on telemedicine programs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported other process and utilization metrics including number of consultations 34,35 and efficiency or timing metrics 27,35,36 . with most showing no differences or improvement. Satisfaction and acceptance from patients, providers, or both was reported in nine studies 12,20,23,27,29,31,34–36 . Most showed that providers and staff had a high rate of satisfaction and felt that telehospitalists followed standards of care with some reporting improved patient care 12,23,27,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Medicine, a highly relationship‐based “team sport,” is another barrier to successful implementation. Whether serving as supervisor or primary attending (as noted in the evaluation by JaKa and colleagues 5 ), the telehospitalist must be “on stage” for both patients and remote spoke colleagues. In our experience, telehospitalists also practice in‐person daytime hospital medicine at spoke sites; this further enhances their relationship and connection with the spoke community and likely contributes to high satisfaction by hub hospitalists and spoke patients and nurses.…”
mentioning
confidence: 99%